Rituximab plus standard of care for treatment of primary immune thrombocytopenia: a systematic review and meta-analysis. Issue 2 (February 2015) - Chugh, Shaan; Darvish-Kazem, Saeed; Lim, Wendy; Crowther, Mark A; Ghanima, Waleed; Wang, Grace; Heddle, Nancy M; Kelton, John G; Arnold, Donald M
Summary: Background: Rituximab is commonly used as a treatment for primary immune thrombocytopenia to induce and maintain remission. The benefit of adding rituximab to standard-of-care treatment is uncertain. Methods: We did a systematic review and meta-analysis of randomised controlled trials assessing the efficacy and safety of rituximab for treatment of adults with primary immune thrombocytopenia. We searched Medline, Embase, and the Cochrane database in duplicate and independently from inception up to July 31, 2014, for relevant studies. Primary outcomes were the proportion of patients achieving a complete platelet count response and a partial platelet count response (as defined in primary studies) that was maintained until the end of follow-up. We also assessed bleeding, infection, and infusion reactions. Findings: Our database search returned 468 abstracts, of which five trials (with total of 463 patients) were eligible for analysis. No patients had splenectomy at the time of enrolment. Median follow-up was 6 months (IQR 6–12). Complete response (>100 × 10 9 platelets per L without rescue therapy) was more common with rituximab than with standard of care (weighted proportions: 46·8% vs 32·5%; relative risk [RR] 1·42, 95% CI 1·13–1·77; p=0·0020). Partial response was not significantly different between groups (57·6% vs 46·7%; RR 1·26, 95% CI 0·95–1·67; p=0·11). Rituximab was not associated with a reduction in bleeding (9·2% vs 5·2%; RR 1·34, 95% CI 0·63–2·87; p=0·44) or an increase in infections (20·1% vs 12·1%; RR 1·40, 95% CI 0·87–2·26; p=0·17). Interpretation: Rituximab can improve complete platelet count responses by 6 months in patients with immune thrombocytopenia. Evidence for sustained responses beyond 6–12 months is limited. Clinicians must consider the goals of treatment before prescribing rituximab. Funding: None.